Targeting the CD47/SIRPα pathway in malignancies: recent progress, difficulties and future perspectives - Jiang, Chenyang; Sun, Hao; Jiang, Zhongxing; Tian, Wenzhi; Cang, Shundong; Yu, Jifeng (Frontiers in Oncology, 2024)
Since its initial report in 2015, CD47 has garnered significant attention as an innate immune checkpoint, raising expectations to become the next "PD-1." The optimistic early stages of clinical development spurred a flurry of licensing deals for CD47-targeted molecules and company mergers or acquisitions for related assets. However, a series of setbacks unfolded recently, starting with the July 2023 announcement of discontinuing the phase 3 ENHANCE study on Magrolimab plus Azacitidine for higher-risk myelodysplastic syndromes (MDS). Subsequently, in August 2023, the termination of the ASPEN-02 program, assessing Evorpacept in combination with Azacitidine in MDS patients, was disclosed due to insufficient improvement compared to Azacitidine alone. These setbacks have cast doubt on the feasibility of targeting CD47 in the industry. In this review, we delve into the challenges of developing CD47-SIRPα-targeted drugs, analyze factors contributing to the mentioned setbacks, discuss future perspectives, and explore potential solutions for enhancing CD47-SIRPα-targeted drug development.